Reading the Hedgehog morphogen gradient by measuring the ratio of bound to unbound Patched protein. - Casali, A.; Struhl, G. (Nature, 2004)
Morphogens are 'form-generating' substances that spread from localized sites of production and specify distinct cellular outcomes at different concentrations. A cell's perception of morphogen concentration is thought to be determined by the number of active receptors, with inactive receptors making little if any contribution. Patched (Ptc), the receptor for the morphogen Hedgehog (Hh), is active in the absence of ligand and blocks the expression of target genes by inhibiting Smoothened (Smo), an essential transducer of the Hh signal. Hh binding to Ptc abrogates the ability of Ptc to inhibit Smo, thereby unleashing Smo activity and inducing target gene expression. Here, we show that a cell's measure of ambient Hh concentration is not determined solely by the number of active (unliganded) Ptc molecules. Instead, we find that Hh-bound Ptc can titrate the inhibitory action of unbound Ptc. Furthermore, we demonstrate that this effect is sufficient to allow normal reading of the Hh gradient in the presence of a form of Ptc that cannot bind the ligand but retains its ability to inhibit Smo. These results support a model in which the ratio of bound to unbound Ptc molecules determines the cellular response to Hh.